Det moderna projektet (Sociologisk Forskning, 2000)
Modernity as a projectModernity as a project with its origin in the Enlightenment, relying on rationality and science, is often ridiculed as old-fashioned and passé by post-modernist philosophers. The rationality involved in modernity is often understood as cold, unemotional instrumental rationality, that is purely as an efficient choice of means to attain given aims or goals. Because of its seeming incompetence in evaluating given goals the Project of Modernity is sometimes looked upon with scepticism even by those who otherwise do not fully endorse the post-modernist critique. By its rejection of religion and traditional morality the Project of Modernity is said to have removed the magic, mystery and sentiment required to maintain a sense of meaning and purpose in human and social life - a disenthrallment in Max Weber's sense. In this paper it is maintained, however, that rationality and emotionality by their interplay can reach beyond instrumental rationality and provide tests of so-called given goals thereby saving the Project of Modernity from accusations of accepting any given goals - even if they are fascist or undemocratic. Goals given by traditional authorities or charismatic leaders can be scrutinised, evaluated and selected or rejected by action involving rationality in a combination with emotionality, it is maintained in this paper.
Keywords: rationality; emotionality; modernity